2006
DOI: 10.1016/s0022-5347(06)00576-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Multitarget Fluorescence In Situ Hybridization Assay to Diagnose Bladder Cancer in Patients With Hematuria

Abstract: The UroVysion fluorescence in situ hybridization assay is significantly more sensitive than voided cytology for detecting bladder cancer in patients evaluated for gross or microscopic hematuria for all grades and stages. Based on these data UroVysion was approved by the Food and Drug Administration for use in patients with hematuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 19 publications
0
79
0
3
Order By: Relevance
“…The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5]. Recently, the UroVysion™ assay for detecting bladder cancer in patients evaluated for gross or microscopic hematuria was also approved by the FDA [6]. Similar to UroVysion FISH probes design, probes specific for centromeres of chromosomes 3, 7, 17 and for the p16 (9p21) locus were used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5]. Recently, the UroVysion™ assay for detecting bladder cancer in patients evaluated for gross or microscopic hematuria was also approved by the FDA [6]. Similar to UroVysion FISH probes design, probes specific for centromeres of chromosomes 3, 7, 17 and for the p16 (9p21) locus were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of probes have been investigated to determine which combination yields the highest sensitivity and specificity for TCC detection, the optimal combination was found to combine CEPs for chromosomes 3, 7, and 17, with a LSI probe to the 9p21 band. This combination significantly increased both the sensitivity and specificity of the assay compared with single probe analysis [5,6,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] Notably, the US Food and Drug Administration has actually approved the use of FISH (UroVysion-Abbott Molecular Inc) for urothelial cancer screening for hematuria and surveillance in known bladder cancer patients. [36] Nevertheless, compared to urine cytology, the routine use of UroVysion is still debatable; this test is a costly method to diagnose clinically insignificant low-grade bladder tumors. [37,38] In addition, the false positive rate related to the presence of benign urothelial umbrella cells with abnormal DNA ploidy makes the routine use of UroVysion relatively unfavorable.…”
Section: Main Body Molecular Markers As a Diagnostic Toolmentioning
confidence: 99%
“…Several comparative studies have demonstrated that the sensitivity of FISH is superior to that of Cytology alone. [28][29][30] Epilogue According to published reports, the happy couple has settled into a mutually satisfying relationship, each helping to complete the other. The future holds additional opportunities for spousal collaboration: many genetic events, originally identified in hematologic and mesenchymal lesions, are being discovered in a variety of carcinomas as well, particularly salivary gland carcinomas.…”
Section: Bladder Cancermentioning
confidence: 99%